2019
DOI: 10.1590/0004-282x20190078
|View full text |Cite|
|
Sign up to set email alerts
|

Consensus of the Brazilian Headache Society on the treatment of chronic migraine

Abstract: Chronic migraine poses a significant personal, social and economic burden and is characterized by headache present on 15 or more days per month for at least three months, with at least eight days of migrainous headache per month. It is frequently associated with analgesic or acute migraine medication overuse and this should not be overlooked. The present consensus was elaborated upon by a group of members of the Brazilian Headache Society in order to describe current evidence and to provide recommendations rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 122 publications
(87 reference statements)
0
19
0
5
Order By: Relevance
“…A enxaqueca crônica é conhecida como uma perturbação de difícil tratamento, em especial quando associado ao uso em excesso de medicamentos. Atualmente, novas terapias para a enxaqueca estão sendo testadas (KOWACS et al, 2019).…”
Section: Resultsunclassified
“…A enxaqueca crônica é conhecida como uma perturbação de difícil tratamento, em especial quando associado ao uso em excesso de medicamentos. Atualmente, novas terapias para a enxaqueca estão sendo testadas (KOWACS et al, 2019).…”
Section: Resultsunclassified
“…Other studies also report that patients with chronic daily headache evidence low concentration and production capacity, anxiety, depression, and hopelessness, and also overlapping two or more psychological disorders. 16,22,24 In this same direction, other research identified that patients diagnosed with migraine were more likely to show complaints related to mood, irritability, difficulties in performing daily tasks, with impaired functionality and quality of life aspects. 25,26 This finding considered pain catastrophization as a process that includes psychosocial factors and correlates with the individual's perception of pain intensity, together with a substantial self-reported functional disability.…”
Section: (C) (D)mentioning
confidence: 90%
“…The scale total is the sum of the scores, and scores range from 0 to 56, and the higher the score, the greater the stress. 15,16 The Pittsburgh Sleep Quality Index was applied to assess the sleep quality of the previous month. The global score ranges from 0 to 21 points, and the highest the score, the worse the quality of sleep.…”
Section: Data Collectionmentioning
confidence: 99%
“…It is also stated that, in patients with CM and MOH, the use of anti-CGRP/R mAbs can be initiated before or after withdrawal of acute medications. Several national headache societies have published recommendations on the use of anti-CGRP/R mAbs for migraines [ 96 , 97 , 98 ].…”
Section: Guidelines For the Use Of Mabs In Migraine (American Headache Society/european Headache Federation)mentioning
confidence: 99%